Antibiotics and the Endocrine System: Mechanisms, Adverse Effects, and Clinical Implications - Łukasz Grabarczyk; Julia Oszytko; Maria Derkaczew; Kamil Sobolewski; Paweł Radkowski (Antibiotics, 2026)
Background/Objectives: Antibiotics are widely used in clinical practice, yet their potential effects on endocrine homeostasis remain insufficiently recognized. This review summarizes endocrine adverse effects associated with selected antibacterial agents, their proposed mechanisms, and clinical relevance. Methods: A narrative literature search was conducted in PubMed/MEDLINE, Scopus, and Web of Science from database inception to 10 August 2026. Clinical, pharmacovigilance, case-based, animal, in vitro, and ex vivo studies were considered. Results: Reported disturbances include SIADH-related hyponatremia, hypoglycemia, altered thyroid hormone metabolism, changes in hypothalamic–pituitary–adrenal axis activity, aldosterone dysregulation, and reproductive hormone disturbances. Selected cephalosporins and carbapenems have been associated with changes in prolactin secretion, thyroid-related parameters, and gonadal function. Fluoroquinolones have been associated with dysglycemia, while effects on reproductive hormone pathways have been reported predominantly in experimental models. Selected macrolides may influence glucocorticoid metabolism and KCNJ5-dependent aldosterone production. Linezolid has been linked to hyponatremia and hypoglycemia, while metronidazole may affect pituitary hormone secretion. Trimethoprim–sulfamethoxazole may contribute to hyponatremia, hyperkalemia, hypoglycemia, and thyroid dysfunction. The supporting evidence is heterogeneous and ranges from case reports and pharmacovigilance analyses to experimental studies. Human clinical evidence is strongest for selected disturbances of glucose and electrolyte homeostasis, whereas many reported reproductive, pituitary, thyroid, and adrenal effects remain supported predominantly by experimental or case-based evidence. Conclusions: Many proposed mechanisms remain incompletely established and cannot be directly extrapolated to routine practice. Awareness of these complications may support earlier recognition, targeted biochemical monitoring, and safer antibiotic therapy, particularly in older, critically ill, or renally impaired patients and those exposed to polypharmacy.